(untitled) (Al-Qamar, 2022)
One of the ancient philosophical arts is the art of Al-Ṭibb (Medical), which has gained great importance in the age of materialism. Even after going through the debates of inspirational and non-inspirational, this art gave a lot of innovation to thought. Ancient philosophers and the people of Sharīʿah have also been speaking on the structure and the nature of various material objects present in this world since ancient time. Islam has also given great importance to this art of medicine through its thoughts, as in the Qur’ān and the sayings of the Messenger of Allah Muhammad (Peace Be Upon Him), many diseases and medicines have been mentioned, and moreover, the names and identities of many herbs are found in many Ḥadīths. Even for the survival of this art, many scholars of this ummah have written books on the name of Al-Ṭibb Al-Nabawī. ʿAbd Al-ʿAzīz Al-Firhārwī was a great scholar of Indo-Pak, who has written a lot on many arts. He has quoted Ḥadīths on his book Al-Tamīz on Medicine and has also described the opinions of some old doctors. Therefore, in this article, we have described the validity of these medical statements as well as contemporary medical thoughts. So, this article will pave the way for researchers to explain the relationship between modern and ancient medicine.